If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 61 = 2x + 17 + x + 17 Reorder the terms: 61 = 17 + 17 + 2x + x Combine like terms: 17 + 17 = 34 61 = 34 + 2x + x Combine like terms: 2x + x = 3x 61 = 34 + 3x Solving 61 = 34 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 61 + -3x = 34 + 3x + -3x Combine like terms: 3x + -3x = 0 61 + -3x = 34 + 0 61 + -3x = 34 Add '-61' to each side of the equation. 61 + -61 + -3x = 34 + -61 Combine like terms: 61 + -61 = 0 0 + -3x = 34 + -61 -3x = 34 + -61 Combine like terms: 34 + -61 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| 2n=10.06 | | 70=7x | | (2x-5)=-6 | | 9.5=v+2.8 | | 8x-6=3x+24 | | (2x-5)=6 | | 15x-8x=49 | | 12*c=108 | | 7y+8=-2y | | 2v+28=16+-4(v+7) | | -2(g+8)=64 | | -2-m=7 | | 4x^2=3x^2+9 | | 5(f-4)=-10 | | -5+5x=35 | | (x-2)=-2x-1 | | 8g-32=4g+16 | | X+17+4x=-29-4x-35 | | 1halfr+6=3-2r | | -10(s+3)=-71 | | (5x^3-6x^2+2x)+(-4x^2+3x)=42 | | 35x^2+76x+32= | | -10(s+3)=71 | | (x-5)=-6x-10 | | 3-2x^2=21 | | 10=-0.15x^2+3x | | t+10=7t+4 | | -8+3x=6+x | | 2-o=-42 | | (x-3)=-6x-17 | | -2+12=12 | | 3n+8-8=-3+2n |